FRI0509 Prevalence of Sarcoidosis and Autoinmune Disease in Not Necrotizing Granulomatosis. (15th July 2016) - Alende, V.; Sopeña, B.; Cameselle Teijeiro, J.; Gonzalez Quintela, A.
Abstract : Background: The diagnosis of not necrotizing granulomatosis (NNG) is very frequent in clinical practice. Physicians often focused their attention on sarcoidosis. However, there are many conditions that can cause this histological diagnosis, including infectous diseases, neoplasms or inflamatory diseases. There ara a few studies into the spectrum of pathologies that cause NNG; consequently, except for sarcoidosis, little information is available (1, 2). Objectives: This study has been designed to determine the prevalence of sarcoidosis and autoinmune diseases in not necrotizing granulomatosis. Methods: We recolected all the tissue samples described as not necrotizing inflammation from 1 January 2010 to 31 december 2014 in the University Hospital of Santiago de Compostela. We recolected socio-demographic, analytical and tissue characteristics. We followed these patients and we described the final diagnosis. Results: During the study period, a total of 290 samples of 207 patients were involved. The 50.7% were women, their mean age was 51, 23 years. Concerning the sample origin, the distribution was as follows: skin 68 (32, 9%), lymphadenopathy 55 (26, 6%), Transbronchial biopsy 30 (14, 5%), lung 12 (5, 8%) and others 42 (20, 2%). Concerning to final diagnosis, we found sarcoidosis 124 (59, 9%); infectous diseases 16 (7, 7%), including tuberculosis infection 8 (4, 0%) and nontuberculous mycobacterial infection 3 (1, 4%); Foreign body granulomatosis 13 (6, 3%); neoplasms 12 (5, 9%); autoinmune disease 6 (3, 1%), 2 of them Wegener granulomatous (0, 9%), 1 chronic polyarticular arthritis (0, 5%), 1 Autoimmune hepatitis (0, 4%), 1 systemic lupus erythematosus (0, 5%) and 1 alopecia (0, 5%); rosacea 3 (1, 4%); Crohn disease 2 (0, 9%); cheilitis 2 (0, 9%) and amyloidosis 1 (0, 5%). The diagnosis was not determinated in 12 patients (5, 9%). Conclusions: The prevalence of sarcoidosis in NNG is almost 50%. However, the autoinmune disease is considerably lower (2, 5%), being Wegener granulomatous the most frequently reported autoinmue disease as it has been described in the literature. The alternative diagnosis most frequent was infectous diseases, including tuberculosis. In 90% of cases, final diagnosis was realized. References: Nazarullah, A., Nilson, R., Maselli, D. J., & Jagirdar, J. (2015). Incidence and aetiologies of pulmonary granulomatous inflammation: A decade of experience. Respirology, 20(1), 115–121. doi:10.1111/resp.12410 Woodard, B. H., Rosenberg, S. I., Farnham, R., & Adams, D. O. (1982). Incidence and nature of primary granulomatous inflammation in surgically removed material. The American Journal of Surgical Pathology, 6(2), 119–29. Retrieved from http://www.ncbi.nlm.nih.gov/pubmed/7102892 /p> Disclosure of Interest: None declared